Valgus knee bracing may have no long-term effect on pain improvement and functional activity in patients with knee osteoarthritis: a meta-analysis of randomized trials - Yinuo Fan; Zhongfeng Li; Haitao Zhang; Guoju Hong; Zhongshu Wu; Weifeng Li; Lixin Chen; Yunlong Wu; Qiushi Wei; Wei He; Zhenqiu Chen (Journal of Orthopaedic Surgery and Research, 2020)
Abstract Background Knee osteoarthritis (KOA), with a high incidence in old-age population, adversely affects their life quality. The valgus knee bracing is an important physical therapy for KOA, but its clinical effects on pain release and functional improvement remained unclear. This meta-analysis is to systematically evaluate the clinical outcomes of valgus knee bracing in patients with KOA. Methods A meta-analysis of clinical randomized controlled trials (RCTs) on pain and functional changes in patients with KOA after using valgus knee braces. The search period was ranged from the inception of the database to May 2020. The enrolled research databases included PubMed, Embase, and Web of Science databases. Two investigators independently formulated inclusion criteria and exclusion criteria and screened and determined the final enrolled literature. Then the outcome indicators were extracted and organized from the included literature, and the risk of bias was assessed by Cochrane Handbook 5.0.1. Results A total of 10 articles were included in this study, including 739 patients. Eight articles were related to the visual analog scale (VAS) pain score, and the results showed that RR = − 0.29, 95% CI − 0.73, 0.15], P = 0.20; four articles were related to the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) function score, and the results showed that RR = − 0.15, 95% CI [− 0.41, 0.11], P = 0.26; two articles were related to the Knee Injury and Osteoarthritis Outcome Score (KOOS), and the results showed that RR = 0.58, 95% CI [− 4.25, 5.42], P = 0.81; and three articles were related to the KOOS Activities of Daily Living (KOOS-ADL), and the results showed that RR = 0.04, 95% CI [− 0.62, 0.69], P = 0.91. These results indicated that the valgus knee bracing has no statistical significance in pain and functional activity improvement of patients with KOA. The subgroup analysis showed that the follow-up time was the source of the heterogeneity of the VAS pain score. Conclusion Our current evidence suggests that valgus knee bracing may not improve pain release and function activates in KOA patients in the long-term period, but only being beneficial to the short-term rehabilitation.